The Crosstalk of mTOR/S6K1 and Hedgehog Pathways - Wang, Yan; Ding, Qingqing; Yen, Chia-Jui; Xia, Weiya; Izzo, Julie G.; Lang, Jing-Yu; Li, Chia-Wei; Hsu, Jennifer L.; Miller, Stephanie A.; Wang, Xuemei; Lee, Dung-Fang; Hsu, Jung-Mao; et al. (Cancer cell, 2012)
Esophageal adenocarcinoma (EAC) is the most prevalent esophageal cancer type in the United States. The TNF-α/mTOR pathway is known to mediate the development of EAC. Additionally, aberrant activation of Gli1, downstream effector of the Hedgehog (HH) pathway, has been observed in EAC. In this study, we found that an activated mTOR/S6K1 pathway promotes Gli1 transcriptional activity and oncogenic function through S6K1-mediated Gli1 phosphorylation at Ser84, which releases Gli1 from its endogenous inhibitor, SuFu. Moreover, elimination of S6K1 activation by an mTOR pathway inhibitor enhances the killing effects of the HH pathway inhibitor. Together, our results established a crosstalk between the mTOR/S6K1 and HH pathways, which provides a mechanism for SMO-independent Gli1 activation and also a rationale for combination therapy for EAC. ► mTOR/S6K1 activates Gli1 in a SMO-independent manner ► Activated S6K1 phosphorylates Gli1 at Ser 84 and promotes Gli1 function ► S6K1-mediated Gli1 activation links the mTOR and HH pathways ► Combination therapy targeting mTOR/HH pathways may provide benefit for EAC therapy